2013
DOI: 10.1016/j.bse.2013.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Low genetic diversity and significant structuring in the endangered Mentha cervina populations and its implications for conservation

Abstract: Eighteen populations of the endangered aromatic and medicinal plant Mentha cervina (Lamiaceae) were sampled across its natural range, in the western half of the Iberian Peninsula, and inter-simple sequence repeats (ISSRs) markers were used to assess genetic diversity and population structure. M. cervina populations exhibited a relatively low genetic diversity (percentage of polymorphic loci PPB ¼ 14.2-58.3%, Nei's genetic diversity H e ¼ 0.135-0.205, Shannon's information index I ¼ 0.08 À 0.33). However, the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 60 publications
2
29
0
Order By: Relevance
“…The H E value is lower than the average value of widespread species (H: 0.22) and is close to the average value of endemic species (H: 0.20) according to the Nybom statistic, which calculated the genetic diversity of many plants at the population level [based on random amplified polymorphic DNA (RAPD), AFLP, and ISSR dominant markers] (Nybom, 2004). This suggested that the high overall genetic diversity that was presented by the species itself could be explained mostly by differences among populations that originated from the high genetic structure (Rodrigues et al, 2013).…”
Section: Genetic Diversity Of B Papyriferasupporting
confidence: 53%
See 3 more Smart Citations
“…The H E value is lower than the average value of widespread species (H: 0.22) and is close to the average value of endemic species (H: 0.20) according to the Nybom statistic, which calculated the genetic diversity of many plants at the population level [based on random amplified polymorphic DNA (RAPD), AFLP, and ISSR dominant markers] (Nybom, 2004). This suggested that the high overall genetic diversity that was presented by the species itself could be explained mostly by differences among populations that originated from the high genetic structure (Rodrigues et al, 2013).…”
Section: Genetic Diversity Of B Papyriferasupporting
confidence: 53%
“…Interestingly, the DM, LH, and HQ populations displayed lower genetic diversity (PPB = 31, 48, and 40%, respectively), while the JS, SP, YJ, HH, and YY populations showed higher genetic diversity (PPB = 54,60,61,55,and 61%,respectively). This indicated that populations in fragmented habitats and with a small effective size are sensitive to stochastic events, genetic drift, and inbreeding, leading to a low genetic diversity and the high genetic structure pattern (Hartl and Clark, 1997;Rodrigues et al, 2013).…”
Section: Genetic Diversity Of B Papyriferamentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, protection of P. ramosissimus on Jeju Island has to firstly begin with protection through in situ conservation, and prevented fragmentation and ruptures. This is because decreases in effective population size lead to stochastic events, genetic drift, and inbreeding, resulting in a decrease of genetic diversity (Hartl and Clark, 1997; Rodrigues et al, 2013). The present habitats of P. ramosissimus need to be protected by conservation areas and there is need to ensure dispersion because of the expected destruction of habitat and decrease of population size.…”
Section: Implications For Conservation and The Origin Of P Ramosissimentioning
confidence: 99%